2018
DOI: 10.1002/lio2.157
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nasal closure on quality of life in patients with hereditary hemorrhagic telangiectasia

Abstract: IntroductionEpistaxis is the most common symptom of hereditary hemorrhagic telangiectasia (HHT). Complete nasal closure is one of the treatment options for patients with severe, intractable epistaxis. In our experience, this surgery can be life changing in a positive sense; but many patients as well as their physicians understandably fear that such a procedure will diminish certain aspects of quality of life (QOL).MethodsCase‐control study of HHT patients treated at the University of Utah HHT Center of Excelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Karapantzos et al reported that 27 HHT patients who were treated with Nd:YAG laser showed improved scores in several dimensions of SF‐36, 2 years postoperatively. Other studies have shown improved HR‐QoL in HHT patients who underwent nasal closure, while patients treated with argon laser, and a combination of septodermoplasty and argon laser showed no significant improvement …”
Section: Discussionmentioning
confidence: 89%
“…Karapantzos et al reported that 27 HHT patients who were treated with Nd:YAG laser showed improved scores in several dimensions of SF‐36, 2 years postoperatively. Other studies have shown improved HR‐QoL in HHT patients who underwent nasal closure, while patients treated with argon laser, and a combination of septodermoplasty and argon laser showed no significant improvement …”
Section: Discussionmentioning
confidence: 89%
“…The risks and benefits should be weighed carefully, especially in patients with HHT. If recurrent epistaxis cannot be controlled conservatively, surgical interventions like nasal occlusion should be considered in an experienced center [ 35 ]. Long-term use of TXA in HHT patients could possibly further damage already strained nasal mucosa and consequently lead to biofilm formation with bacterial colonization, chronic inflammation and nasal congestion.…”
Section: Discussionmentioning
confidence: 99%
“…Our study does not highlight changes in the quality of life followed by nasal closure, but pictures a substantial improvement in general health and reduction in epistaxis and daily bleedings. Previous studies have linked reduced epistaxis to increase the quality of life (QOL), using epistaxis severity score (ESS) as a   surrogate measure for QOL [19,20]. As of 2018, each HHT center has its own criteria for selecting patients for nasal closure.…”
Section: Discussionmentioning
confidence: 99%